IL-36 Cytokines: Their Roles in Asthma and Potential as a Therapeutic - Dong, Hongna; Hao, Yuqiu; Li, Wei; Yang, Wei; Gao, Peng (Frontiers in Immunology, 2022)
Interleukin (IL)-36 is a member of IL-1 superfamily, consisting of three agonists of IL-36α, IL-36β, IL-36γ and an IL-36 receptor antagonist (IL-36Ra). IL-36 is crucial for immune and inflammatory responses. The abnormal levels of IL-36 expression are involved in the pathogenesis of inflammation, autoimmunity, allergy and cancer. Here, we summarize recent reports that IL-36 participates in the pathogenesis of inflammatory diseases and the potential mechanisms underlying their roles in asthma. Abnormal levels of IL-36 are associated with the pathogenesis of different types of asthma by regulating the functions of a variety of cells. Considering the important role of IL-36 in asthma, IL-36 may become a potential therapeutic target for asthma treatment. However, the existing evidence is insufficient to fully elucidate the specific mechanisms underlying the action of IL-36 during the pathological process of asthma. The possible mechanisms and functions of IL-36 in different types of asthma need further studies.